Exploring Lumacaftor: a novel antibacterial approach for treating E. coli-induced urinary tract infections - G., Anjali; M., Lakshmi; B., Deepika Srija; M., Ushaswini; K., Neeraja; T. C., Venkateswarlu; V., Anuradha; Kante, Meenakshi (International Journal of Research in Medical Sciences, 2025)
Background: Urinary tract infections (UTIs) are primarily caused by Escherichia coli (E. coli), among the most common bacterial infections internationally. Oxygen-insensitive NADPH nitro reductase (NFSA), a vital protein in E. coli, plays a major role in the development of UTIs. Present NFSA-inhibiting drugs, such as nitrofurantoin, have limitations, including adverse effects, reduced effectiveness, and confront against drug-resistant strains. This study suggests Lumacaftor as a potential lead compound to target NFSA, given its promising pharmacological profile. Methods: The study recognized NFSA as the important target protein and performed virtual screening of compounds from the Drug Bank database via AutoDock Vina. The pharmacokinetics of the most excellent candidates were evaluated, and molecular dynamics simulations (100 ns) carried out using Desmond further validated the strength and binding efficacy of the preferred leads. Results: The molecular docking study noted Lumacaftor as the most capable NFSA inhibitor, attained a docking score of -10.02 kcal/mol, indicating the strongest expected binding affinity among the screened compounds. The predicted pharmacokinetic properties of Lumacaftor, Phthalocyanine, and Nitrofurantoin exposed key differences that carry the suitability of Lumacaftor as a potential NFSA inhibitor. Furthermore, Lumacaftor revealed a relatively low average ligand RMSD in relation to the protein (5.146 Å) and itself (2.073 Å), suggestive of stable binding within the active site of the NFSA protein. Conclusions: This study successfully acknowledged and validated NFSA as a therapeutic target for E. coli causing UTIs, addressing the limitations of current treatments, including antibiotic resistance and reduced pharmacological efficiency.